(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aimed to measure the nature of the correlation relationship and the effect between the ‘’independent variable’’ strategic capabilities of the banks of its dimensions represented by the (Technological, Marketing, Administrable, creative) capabilities, and the ‘’dependent variable’’ building intelligent organizations of its dimensions represented by (environment understanding, strategic vision, excellence, and collective intelligence ). Whereas increasing obstacles that banks facing today, it has become urgent necessity to adopt the concept of intelligent organization to keep up with changes and technological development, achieving by a radical transformation in the methods and ways of its banking services through the existence of qualified capable administration staff to face the challenges and adapt it, that is subjected to what the banks’ ownership of strategic capabilities which is considered as a primary source to achieve success and excellence, so the research issue is determined by the questioning of ( what is the correlation nature and the effect between the banks’ strategic capabilities and building the intelligent organizations?), the research relied on the descriptive and analytical approach, and the questionnaire employed as a main tool in data collection from the researched sample in the (medium, and executive) levels of administration in the Iraqi Private Commercial Banks represented by (Baghdad, Al Mansour for investment, Gulf commercial, Middle East) and data was analyzed by the statistical program (spss v.28) in calculating (weighted arithmetic mean, standard deviation, coefficient of variation, Person correlation coefficient, (t) test, regression coefficient, interpretation coefficient(R squared), (F) test. The research has reached a number of results the most prominent was: having correlation relationship and moral impact for the strategic capabilities to the researched banks in building intelligent organizations. As strategic capabilities dimensions for the researched banks were able to explain the ongoing changes in building the intelligent organizations with a rate of (%48).